Different variation behaviors of resistivity for high-temperature-grown and low-temperature-grown p-GaN films - 杨静 赵德刚 江德生 陈平 刘宗顺 朱建军 乐伶聪 李晓静 何晓光 张立群 杨辉 (Chinese physics B, 2016)
Two series of p-GaN films grown at different temperatures are obtained by metal organic chemical vapor deposition（MOCVD）. And the different variation behaviors of resistivity with growth condition for high- temperature（HT）-grown and low-temperature（LT）-grown p-GaN films are investigated. It is found that the resistivity of HT-grown p-GaN film is nearly unchanged when the NH_3 flow rate or reactor pressure increases. However, it decreases largely for LT-grown p-GaN film.These different variations may be attributed to the fact that carbon impurities are easy to incorporate into p-GaN film when the growth temperature is low. It results in a relatively high carbon concentration in LT-grown p-GaN film compared with HT-grown one. Therefore, carbon concentration is more sensitive to the growth condition in these samples, ultimately,leading to the different variation behaviors of resistivity for HT- and LT-grown ones.